2006
DOI: 10.1016/j.neuropsychologia.2005.12.006
|View full text |Cite
|
Sign up to set email alerts
|

Bias in magnitude estimation following left hemisphere injury

Abstract: There is a growing interest both in identifying the neural mechanisms of magnitude estimation and in identifying forms of bias that can explain aspects of behavioral syndromes like unilateral neglect. Magnitude estimation is associated with activation of temporo-parietal cortex in both cerebral hemispheres of normal subjects; however, it is unclear if and how left hemisphere lesions bias magnitude estimation because the infrequency of neglect and the presence of aphasia in these subjects confound examination. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
20
0
2

Year Published

2008
2008
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(25 citation statements)
references
References 25 publications
3
20
0
2
Order By: Relevance
“…One issue that may be developed more fully in ATOM is that of hemispheric asymmetries (see Woods et al 2006;Niemeier et al 2007). Owing to the association of numerical mapping with space, there is an emphasis on right hemisphere functions, but it is clear that explicit numerical operations and motor action selection and preparation rely on left parietal cortex mechanisms.…”
Section: Atom Revisitedmentioning
confidence: 99%
“…One issue that may be developed more fully in ATOM is that of hemispheric asymmetries (see Woods et al 2006;Niemeier et al 2007). Owing to the association of numerical mapping with space, there is an emphasis on right hemisphere functions, but it is clear that explicit numerical operations and motor action selection and preparation rely on left parietal cortex mechanisms.…”
Section: Atom Revisitedmentioning
confidence: 99%
“…Woods et al 2006;for reviews: Walsh 2003;Bueti and Walsh 2009) can be associated with left or right-hemisphere structures, and dominances can switch depending on a variety of factors, for example dexterous actions such as finger counting might be more closely associated with magnitude processes in the left hemisphere (Bueti and Walsh 2009), thus giving rise to TMS-induced symptoms similar to Gerstmann's syndrome (Rusconi et al 2005). A different example is the SNARC effect, so the observation that responses in left and right space speed up judgements about small and large numbers, respectively (Dehaene et al 1993), with a possible link to biases and crossover observed for the bisection of mental number lines (Zorzi et al 2002).…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, several studies have investigated the ability of pharmacological agents to ameliorate spatial bias in patients with neglect (Müller, 2008;Malhotra et al, 2006;Woods et al, 2006;Mukand et al, 2001;Geminiani et al, 1998;Grujic et al, 1998;Hurford et al, 1998;Fleet et al, 1987), and have, with the exception of one study (Grujic et al, 1998), found generally encouraging results. However, most of these studies have tested either a single patient or a very small sample of patients, making it difficult to generalize results.…”
Section: Discussionmentioning
confidence: 99%
“…There have been a number of promising attempts to investigate the potential benefits of different stimulants in patients with left spatial neglect (Malhotra, Parton, Greenwood, & Husain, 2006;Woods et al, 2006;Mukand et al, 2001;Geminiani, Bottini, & Sterzi, 1998;Grujic et al, 1998;Hurford, Stringer, & Jann, 1998;Fleet, Valenstein, Watson, & Heilman, 1987). However, the work with patients raises the same important caveats that applied to behavioral manipulations of alertness, that is, is this a general effect of symptom reduction or a spatially specific effect?…”
Section: Introductionmentioning
confidence: 99%